Quantitative assessment of oral phase efficiency: validation of the Test of Masticating and Swallowing Solids (TOMASS). Issue 3 (21st January 2019) - Lamvik‐Gozdzikowska, Kristin; Guiu Hernandez, Esther; Apperley, Olivia; McIntosh, Theresa; Huckabee, Maggie‐Lee
Abstract: Background: The Test of Masticating and Swallowing Solids (TOMASS) has been developed to provide clinicians with objective data regarding the efficiency of oral phase function and solid bolus ingestion. Aims: To determine if the TOMASS will detect changes in the oral phase of swallowing imposed by topical anaesthesia, thus providing validation of its clinical utility. Methods & Procedures: Per the standard protocol, 10 healthy participants ate one‐quarter of an Arnotts Salada TM biscuit. The number of bites per cracker, number of masticatory cycles, number of swallows and total time taken were recorded at baseline, following application of topical oral anaesthetic; this was additionally compared with a post‐anaesthetic condition. Median and interquartile range (IQR) were calculated. Wilcoxon signed‐rank tests were conducted to evaluate trial effect, and Friedman's tests were used to detect differences in the number of bites, number of swallows, number of chews and time taken to eat the crackers. Outcomes & Results: Results indicated that the number of both bites and swallows did not significantly change across conditions ( χ ²(2) = 0.105, p = 0.949, χ ²(2) = 1.357, p = 0.507); however, the number of chews for the anaesthetic condition was significantly higher when compared with the baseline ( p = 0.02) and post‐anaesthesia conditions ( p = 0.02). Further, the durations of ingestion in the anaesthetic condition were significantly longer than the baseline ( p = 0.01) and post‐anaesthesia ( p = 0.01) conditions. Across all measures, there were no differences between baseline and post‐anaesthesia conditions. Conclusions & Implications: Although further exploration is required, these early data suggest the TOMASS is a sensitive measure in the evaluation of the oral‐phase preparation of solid textures.